Perbedaan Hasil Jadi Tas Hiasan Kerang Dengan Menggunakan Bahan Pelapis Fushible Interfacing - PRIHATININGRUM, WINDA (Universitas Negeri Surabaya, 2013)
Abstract The purpose of this research was to find out the finished result of the bag with shells decoration using the Woven Fushible Interfacing of type LP 155, to find out the finished results of the bag with shells decoration using Knit Fushible Interfacing of type 7403, to find out the finished results of the shells decoration bag using the Weft Insertion Fushible Interfacing, to know the difference between the finished results of the bag using a coating material of Woven Fushible Interfacing of type LP 155, Knit Fushible Interfacing of type 7403, and Weft Insertion Fushible Interfacing of type 2613 and to know the best results from the finished results of the shell waste decoration bag by using the coating materials of Woven Fushible Interfacing of type LP 155, Knit Fushible Interfacing of type 7403, and Weft Insertion Fushible Interfacing of type 2613. The research method used the observation method, The overall of single anava results indicated < 0.05 thus the overall was significant. The mean value on the highest mean first aspect was the woven fushible interfacing of type LP155 with mean of 3.55, the second aspect of woven fushible interfacing of type LP155 the mean was 2.82, the third aspect of woven fushible interfacing of type LP155 the mean was 2.81, the fourth aspect of woven fushible interfacing of type LP155 the mean was 3.94. Based on the results obtained, it could be concluded that the best result was the woven fushible interfacing of type LP155. Keywords: Bags, shells decoration and Fushible interfacing. Abstrak Tujuan penelitian ini adalah untuk mengetahui hasil jadi tas dengan hiasan kerang yang menggunakan Woven Fushible Interfacing tipe LP 155, untuk mengetahui hasil jadi tas dengan hiasan kerang yang menggunakan Knit Fushible Interfacing tipe 7403, untuk mengetahui hasil jadi tas hiasan kerang menggunakan Weft Insertion Fushible Interfacing, untuk mengetahui perbedaan hasil jadi tas antara yang menggunakan bahan pelapis Woven Fushible Interfacing tipe LP 155, Knit Fushible Interfacing tipe7403, dan Weft Insertion Fushible Interfacing tipe 2613 dan untuk mengetahui hasil yang terbaik dari hasil jadi tas hiasan limbah kerang dengan menggunakan bahan pelapis Woven Fushible Interfacing tipe LP 155, Knit Fushible Interfacing tipe7403, dan Weft Insertion Fushible Interfacing tipe 2613. Metode penelitian menggunakan metode observasi, Keseluruhan hasil anava tunggal menunjukan < 0,05 maka keseluruhan signifikan. Nilai mean pada aspek pertama mean tertinggi adalah woven fushible interfacing tipe LP155 mean 3.55, aspek kedua woven fushible interfacing tipe LP155 mean2,82, aspek ke tiga woven fushible interfacing tipe LP155 mean 2,81, aspek keempat woven fushible interfacing tipe LP155 mean 3,94. Berdasarkan hasil yang diperoleh maka dapat disimpulkan bahwa hasil yang terbaik adalah woven fushible interfacing tipe LP155. Kata kunci :Tas, hiasan kerang dan Fushible interfacing